Do Significant Labor Market Events Change Who Does the Chores? Paid Work, Housework and Power in Mixed-Gender Australian Households - Gigi Foster; Leslie S. Stratton (Institute of Labor Economics (IZA), 2017)
We examine how men and women in mixed-gender unions change the time they allocate to housework in response to labor market promotions and terminations. Operating much like raises, such events have the potential to alter intra-household power dynamics. Using Australian panel data, we estimate couple-specific fixed effects models and find that female promotion has the strongest association with housework time allocation adjustments. These adjustments are in part attributable to concurrent changes in paid work time, but gender power relations also appear to play a role. Further results indicate that households holding more liberal gender role attitudes are more likely to adjust their housework time allocations after female promotion events. Power dynamics cannot, however, explain all the results. Supporting the sociological theory that partners may 'do gender', we find that in households with more traditional gender role attitudes, his housework time falls while hers rises when he is terminated.
Keywords: D13; J10; 330; time use; intra-household allocation; gender; housework